Pemanfaatan Augmented Reality dalam Pembelajaran IPS Menyajikan Informasi Sejarah dengan Realitas Tambahan - Nabila Putri Wahiddiyah; Ayudhia Nur Luthfia; Desy Safitri; Sujarwo Sujarwo (Universitas Maritim AMNI Semarang, 2023)
Utilization of Augmented Reality (AR) in learning Social Sciences (IPS) with a focus on presenting historical information. Augmented Reality is a technology that allows users to see the real world with the addition of digital elements, such as images, text, or 3D objects inserted in the physical environment. This research illustrates how AR can be used in social studies learning to improve students' understanding of history. By integrating AR into the learning experience, students can access additional information visually and interactively. For example, they can